Time-Frequency and Time-Scale-Based Fragile Watermarking Methods for Image Authentication. (9th August 2010) - Barkat, Braham; Sattar, Farook
Abstract : Two fragile image watermarking methods are proposed for image authentication. The first method is based on time-frequency analysis and the second one is based on time-scale analysis. For the first method, the watermark is chosen as an arbitrary nonstationary signal with a particular signature in the time-frequency plane. Experimental results show that this technique is very sensitive to many attacks such as cropping, scaling, translation, JPEG compression, and rotation, making it very effective in image authentication. For the second method, based on a wavelet-domain multiresolution analysis, quantization index modulation (QIM) embedding scheme and arbitrary frequency-modulated (FM) chirp watermarks are used in the implementation. In this blind technique, the original watermark is needed neither for the content integrity verification of the original image nor for the content quality assessment of the distorted image.